Phenotyping nematode feeding sites: three‐dimensional reconstruction and volumetric measurements of giant cells induced by root‐knot nematodes in Arabidopsis. Issue 2 (22nd January 2015) - Cabrera, Javier; Díaz‐Manzano, Fernando E.; Barcala, Marta; Arganda‐Carreras, Ignacio; de Almeida‐Engler, Janice; Engler, Gilbert; Fenoll, Carmen; Escobar, Carolina
Summary: The control of plant parasitic nematodes is an increasing problem. A key process during the infection is the induction of specialized nourishing cells, called giant cells (GCs), in roots. Understanding the function of genes required for GC development is crucial to identify targets for new control strategies. We propose a standardized method for GC phenotyping in different plant genotypes, like those with modified genes essential for GC development. The method combines images obtained by bright‐field microscopy from the complete serial sectioning of galls with Trak EM2, specialized three‐dimensional (3D) reconstruction software for biological structures. The volumes and shapes from 162 3D models of individual GCs induced by Meloidogyne javanica in Arabidopsis were analyzed for the first time along their life cycle. A high correlation between the combined volume of all GCs within a gall and the total area occupied by all the GCs in the section/s where they show maximum expansion, and a proof of concept from two Arabidopsis transgenic lines (J0121 ≫ DTA and J0121 ≫ GFP) demonstrate the reliability of the method. We phenotyped GCs and developed a reliable simplified method based on a two‐dimensional (2D) parameter for comparison of GCs from different Arabidopsis genotypes, which is also applicable to galls from different plant species and in different growing conditions, as thickness/transparency is not a restriction.